Application of PRP combined thread lifting with absorbable barbed PPDO threads in facial rejuvenation - Ju Tian; LiuHangHang Cheng; Xiao Cui; Min Xuan; Yu Yang; Zhifang Zheng; Biao Cheng (Innovative Journal of Medical and Health Sciences, 2023)
Background and Objective: Over the years, the use of platelet-rich plasma (PRP) and thread lifting in facial rejuvenation has become increasingly widespread. However, it is still difficult to fully meet the expectations of patients and therapists using PRP alone or thread-lifting alone. The objective of this study was to observe the synergistic effect of PRP and thread lifting on facial rejuvenation. Methods: Between January 2015 and September 2017, 30 patients (2 men and 28 women) were selected for this study. Combined use of PRP and thread-lifting with absorbable barbed poly(para-dioxanone)(PPDO) threads for facial rejuvenation. Efficacy and adverse effects were investigated by patients and physicians at the end of the treatment. Results: 28 of the 30 participants completed the treatment and study and were followed up for 3–12 months. After a series of treatments, most of the participants achieved satisfactory results. The total subjective satisfaction scores assessed by the participants and physicians were 89.28% and 92.86%, respectively. No serious complications, such as allergies, severe swelling, hemorrhage, infection, or nerve damage, were found. Conclusion: The combined use of PRP and thread lifting is a safe and effective method for facial rejuvenation, with a lower risk of complications. Abbreviations: ECM = extracellular matrix, PPDO = poly(para-dioxanone), PRP = platelet-rich plasma.